Mitigating disaster in Mozambique - International Potato Center (2013)
Working closely with government extension personnel, a two year effort to mitigate the impact of disasters in 5 provinces of Mozambique succeeded in getting new drought-tolerant o0range-fleshed sweetpotato varieties distributed to over 134,000 households.